2018
DOI: 10.1186/s13293-018-0182-x
|View full text |Cite
|
Sign up to set email alerts
|

The association between cannabis use and suicidal behavior in patients with psychiatric disorders: an analysis of sex differences

Abstract: BackgroundCannabis is the most commonly used illicit drug. In the general population, its use has been linked to a heightened propensity for suicidal behavior (SB). We hypothesize that this association varies in patients with psychiatric disorders. SB is known to vary by sex and therefore an investigation of cannabis’ association with SB must consider sex differences. The purpose of this study is to investigate the association between cannabis use and suicide attempts in men and women with psychiatric disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…This prevalence in those with OCS is interesting, given that psychosis, but not OCD, has been strongly associated with use of or dependence on cannabis (45). Such an association has been found for other psychiatric disorders, including depression, anxiety, and suicide attempts, and for psychosis manifested at earlier ages (45)(46)(47)(48). We do not, however, know of its effect on OCS or on the development of psychosis.…”
Section: Discussionmentioning
confidence: 90%
“…This prevalence in those with OCS is interesting, given that psychosis, but not OCD, has been strongly associated with use of or dependence on cannabis (45). Such an association has been found for other psychiatric disorders, including depression, anxiety, and suicide attempts, and for psychosis manifested at earlier ages (45)(46)(47)(48). We do not, however, know of its effect on OCS or on the development of psychosis.…”
Section: Discussionmentioning
confidence: 90%
“…These characteristics are commonly adjusted for in the literature, and were chosen due to their clinical relevance or possible confounding. 13 16 Goodness of fit was assessed using the Hosmer-Lemeshow test and McFadden's pseudo R 2 . 17 , 18 …”
Section: Methodsmentioning
confidence: 99%
“…Our team has previously shown that amongst a different sample of patients with psychiatric comorbidities, more frequent cannabis use was associated with a higher risk of suicide attempt in men, but not women. 13 We measured frequency of cannabis use as a binary variable, categorized into daily use or less than daily use. All analyses were performed using STATA version 13.0.…”
Section: Methodsmentioning
confidence: 99%
“…However, a longitudinal study conducted in 2009 found no increase in suicide completion in cannabis users [101], and an additional meta-analysis of the literature conducted in 2016 reported no clear evidence to support cannabis use as a risk factor for suicidality [102]. In addition, cannabis users with pre-existing depression may experience increased suicidal ideation [103], although conflicting findings showing no increase in suicidal ideation have also been reported [104]. Similar to the findings in individuals with pre-existing anxiety, cannabis use in patients with preexisting depression is associated with worse recovery of symptoms and outcomes [105].…”
Section: Association With Anxiety and Depressionmentioning
confidence: 99%